Terapi Healing The Mind Untuk Mengatasi Kondisi Traumatik Pada Anak Dan Remaja Korban Kekerasan Seksual - Pangesti, Nova Ari; Saputri, Dita Ayu Nur (Institut Citra Internasional, 2024)
Sexual violence against children continues to be a serious threat. The most urgent impact of sexual violence is that children will have deep trauma that can disrupt growth and development. Children are vulnerable to experiencing post-traumatic stress disorder (PTSD) which is characterized by the desire to commit suicide, increased anxiety, restlessness, worry about the future, and the desire to become a perpetrator of sexual violence in the future. One of the non-pharmacological treatments for victims of sexual violence who have experienced trauma is Healing the Mind therapy with a research innovation that combines art therapy and spirituality. Objective research analyze the effect of Healing The Mind therapy in overcoming trauma in children and adolescents who have experienced sexual violence. Method this research is a type of qualitative research that applies exploratory research methods by applying in-depth interview techniques. Data analysis using Collaizi. Results there are three main themes identified in this research, namely (1) Conditions of trauma felt before being given healing the mind therapy which consists of 3 sub themes (2) Conditions of trauma felt before being given Healing The Mind therapy which consists of 1 sub theme (3) Effectiveness of Healing The Mind therapy which consists of 4 sub themes. Conclusion four participants stated that the feelings experienced by each participant were different after the incident of sexual violence. Healing the mind therapy has the ability to reveal unexpressed emotions, reduce the level of trauma, and create a sense of calm in the individual.